Real-life treatment of cluster headache in a tertiary headache center – results from the Danish Cluster Headache Survey - Petersen, Anja Sofie; Lund, Nunu; Jensen, Rigmor Højland; Barloese, Mads (Cephalalgia, 2021)
Background Pharmacological treatment of cluster headache constitutes the core of clinical management, but evidence is sparse. We aimed to generate insight in the existing treatment and identify associations between clinical features and treatment response. Methods Patients aged 18–65 diagnosed with cluster headache according to the ICHD-2 completed a questionnaire followed by a structured interview. Multiple logistic regression was used to identify associations. Results The population consisted of 400 patients with an episodic: chronic ratio of 1.7:1. Episodic patients were more likely to respond to triptans (odds ratio = 1.77, confidence interval: 1.08–2.91, p = 0.023) and oxygen (odds ratio = 1.64, confidence interval: 1.05–2.57, p = 0.031) than chronic. Oxygen response was less likely if pain intensity was very severe (odds ratio = 0.53, confidence interval: 0.33–2.57, p = 0.006) and the risk of a poor response increased with disease duration (odds ratio = 0.79, confidence interval: 0.65–0.96, p = 0.016). Among current users of sumatriptan injection and oxygen, the proportion achieving 100% relief was higher with sumatriptan injection (p > 0.001) than with oxygen. No associations were identified regarding verapamil. Only 57% of current users of preventive medication responded at a 50% level. Conclusion Episodic cluster headache is more responsive to acute therapy than chronic. Further, sumatriptan injection was more effective than oxygen and the responder-rate was limited with verapamil. More effective acute and preventive therapies are needed for cluster headache patients.